Characteristics of residual oil fly ash and their utility for construction purposes - faten mustafa slaty; Islam Al-Dabsheh; Taleb Odeh (Kuwait Journal of Science)
The present work investigates the physical and chemical characteristics of the residual oil fly ash (ROFA), generated as a by-product or industrial waste from burning heavy fuel oil in power plants. A possibility of re-utilization of ٍthe ROFA for construction purposes was estimated by activation of the ROFA with cementitious materials as a hardened paste matrix. The physical properties of the ROFA showed low bulk density, 0.21g/cm3 and water content, 0.33%, as compared with literature. The particle size is less than 120μm. The chemical analysis showed that the ROFA composes mostly of carbon, about 69% and 7% sulfur with residue ash. In addition, significant amount of heavy metals, such as Sr, Ti, Zn, V, Cr and Ni are detected. The XRD data confirmed that, the ROFA is mainly composed of amorphous carbon with metallic sulfates and metallic oxide materials. In order to investigate the changes of the hardened paste strength when the ROFA is added to the mixture, a reference mixture was performed. Also, the changes of the density was estimated. The results indicated that, the addition of 10, 20, and 30 wt.% of ROFA shows a remarkable decrease in both. This study has found that the ROFA has the potential to be re-utilized with cementitious material as light weight material, or as a black pigment, which provides a good changes of the hardened paste color and density.